Protection role of national human rights institutions - Ramcharan, B. G. (Leiden ; Boston : Martinus Nijhoff Publishers, 2005)
This volume offers a wealth of information on the protection functions of existing national human rights institutions in a wide range of countries, drawn from Asia, Africa, Europe, Latin America and Oceania. These essays together make clear the genuine striving by national human rights commissions to act for the protection of human rights in the countries they serve, and the variety of protection models that can be and are being adopted, both in developed and developing countries.
The protection role of the Australian Human Rights Commission / John von Doussa -- The protection role of the Danish Human Rights Commission / Morten Kjaerum -- The protection role of the Fiji Human Rights Commission / Shaista Shameem -- The protection role of the Ghana Human Rights Commission / Anna Bossman -- The protection role of the Mexican Human Rights Commission / Jose Luis Soberanes Fernandez -- The protection role of the Nepalese Human Rights Commission / Nayan Bahadur Khatri -- The protection role of the Northern Ireland Human Rights Commission / Brice Dickson -- The protection role of the Philippines Human Rights Commission / Purificacion C.V. Quisumbing -- The protection role of the Uganda Human Rights Commission / Margaret Sekaggya -- National institutions and the protection of economic, social and cultural rights / Orest Nowosad.
Includes bibliographical references (pages 195-197).
Keywords: National human rights institutions; Droits de l'homme.; 2; 2; 2; National human rights institutions; Droits de l'homme.; Ligues des droits de l'homme.